The impact of COVID-19 on a cohort of origin residents and internal migrants from South Africa's rural northeast - Carren Ginsburg; Mark A. Collinson; F. Xavier Gómez-Olivé; Sadson Harawa; Chantel F. Pheiffer; Michael J. White (Elsevier, 2022)
South Africa has a large temporary migrant population with people commonly moving to metropolitan areas to access employment, while maintaining links with their rural origin households. The COVID-19 pandemic has impacted patterns of movement, livelihoods and health seeking, and the effects on internal, temporary migrants are unclear. Using longitudinal data spanning 2018 to 2020, this paper employs descriptive statistics and regression analyses to assess the impacts of COVID-19 on a cohort of 2971 persons aged 18-40 at baseline, both residents and migrants, from a rural district in South Africa's northeast. In contrast with 2018-2019, in 2020 the share of rural residents initiating a migration decreased by 11 percentage points (p<0.001), while the share of temporary migrants returning to origin households increased by 5 percentage points (p<0.001). Study participants who were continuing migrants reported fewer job losses in comparison with rural-stayers, while 76% of return migrants who were employed in 2019 were no longer employed in 2020. Further, among those who did not experience food shortages in 2019, rural-stayers had 1.42 times the odds of continuing migrants of suffering shortages in 2020. In 2020 health service use in the cohort decreased overall, with return migrants having still lower odds of utilising health services. The results highlight the differential geographic and socioeconomic manifestations of the pandemic, with worsening socioeconomic circumstances observed for rural-staying (disproportionately female) and returning populations, while continuing migrants fared relatively better. It is vital that a COVID-19 response considers the potentially heterogeneous impact of the pandemic on mobile and stable populations. Policy responses may include targeting migrants at their destinations in health promotion of COVID-19 messaging, and strengthening health care and social support in origin communities in recognition that these areas receive return migrants into their catchment population.